An evaluation of parent preference for prompting procedures. Issue 2 (26th July 2019) - Halbur, Mary E.; Kodak, Tiffany; Wood, Raven; Corrigan, Erin
Abstract : Parent participation in intervention can enhance intervention efficacy and promote generalization of skills across settings. Thus, parents should be trained to implement behavioral interventions. The purpose of the current investigation was to evaluate parent preference for and acceptability of 3 commonly used prompting procedures. We trained parents of children with disabilities to use 3 empirically validated prompting strategies (i.e., least‐to‐most, most‐to‐least, and a progressive‐prompt delay). Once the parent reached the mastery criteria with each prompting procedure, we evaluated his/her preference for each of the procedures using a concurrent‐chains arrangement. We also measured treatment acceptability of all procedures throughout the study. All participants met the mastery criteria for each of the prompting procedures and showed a preference for least‐to‐most prompting. Results suggest parents' acceptability of procedures prior to training were different than posttraining/post‐child practice. In addition, acceptability rating scores obtained at the end of the investigation corresponded to preference of intervention during the concurrent‐chains arrangement. The results demonstrate the benefits of objective measures for studying preference for behavioral, skill‐acquisition procedures.